(3bdGOI GdfMQ aj hajGJ CYjGf GdOgQs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHGbi HYO afGA Ndbg CeG HYO aEfg deG cGf GdJGQjN WQjbkG Edi GdYde CQOJ Cf CLeY ajg eLehYkG dGFbkG hQJHJg Ydi GdSff eHJOFkG HChd SfI ef GdgLQI LGYdkG cd eGFI SfI NeS WHbGJ s
(3BNQgG (B:s
(3GdSfI Gdehajg YTQjf HYO GdKdGKeGFI hajgG GdMGaX CHh YHO Gddg eMeO Hf jhSa Hf eWQ GdZQHQi hGdEeGe GdcHjQ CHh Ydi Hf NjQGf Je GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3fSNI NRGFfjI eeG fSN dCejQ GdeDefjf GdeDjO HGddg eMeO Hf GdbGSe Hf eMeO Hf QShd SfI (B1035 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI GdMSjfi (B(19) s
Keywords: (3GdJGQjNs